Constrained caloric curves for hot nuclei - Borderie B. (EPJ Web of Conferences, 2012)
Simulations based on experimental data obtained from multifragmenting quasi-fused nuclei produced in central 129Xe + natSn collisions have been used to deduce event by event freeze-out properties on the thermal excitation energy range 4–12 AMeV. From such properties, information on constrained caloric curves has been derived. At constant average volumes caloric curves exhibit a monotonous behavior whereas for constrained pressures backbending is observed. Such results support the existence of a first order phase transition for hot nuclei.